Healthcare utilisation and empowerment among women in Liberia. Issue 11 (8th August 2013) - Sipsma, Heather; Callands, Tamora A; Bradley, Elizabeth; Harris, Benjamin; Johnson, Billy; Hansen, Nathan B
Abstract : Background: Many efforts have been undertaken to improve access to healthcare services in low-income settings; nevertheless, underutilisation persists. Women's lack of empowerment may be a central reason for underutilisation, but empirical literature establishing this relationship is sparse. Methods: We conducted a cross-sectional study using data from the 2007 Liberia Demographic and Health Survey. Our sample included all non-pregnant women who were currently married or living with a partner (N=3925 unweighted). We used multivariate logistic regression to assess the associations between constructs derived from the Theory of Gender and Power (TGP) and healthcare utilisation. Results: Two-thirds of women (65.6%) had been to a healthcare facility for herself or her children in the past 12 months. Constructs from the three major theoretical structures were associated with healthcare utilisation. Women with no education, compared with women with some education, were less likely to have been to a healthcare facility (OR=0.76; 95% CI 0.62 to 0.93) as were women who had experienced sexual abuse (OR=0.65; 95% CI 0.45 to 0.95) and women who were married (OR=0.69, 95% CI 0.54 to 0.88). Women in higher wealth quintiles, compared with women in the next lower wealth quintile, and women with more decision-making power had greater odds of having been to a healthcare facility (OR=1.22; 95% CI 1.10 to 1.36 and OR=1.10; 95% CI 1.01 to 1.20; respectively). Conclusions: Strong associations exist between healthcare utilisation and empowerment among women in Liberia, and gender imbalances are prevalent. This fundamental issue likely needs to be addressed before large-scale improvement in health service utilisation can be expected.